EFEKTIVITAS ASAS PACTA SUNT SERVANDA SAAT TERJADI KEADAAN MEMAKSA (FORCE MAJEURE) DALAM HUKUM PERJANJIAN INDONESIA - Farhan Jiddan Saros; Nurkholis Anwar (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The effectiveness of the Pacta Sunt Servanda principle in Indonesian treaty law becomes an important subject when force majeure occurs. This principle implies the obligation of parties to comply with the agreed contents of the agreement. However, when events beyond control, such as natural disasters, war, or other unexpected events (force majeure), this principle becomes tested. In this context, the effectiveness of the Pacta Sunt Servanda principle in Indonesian treaty law requires a balance between adherence to the agreed agreement and recognition of unforeseen circumstances that may affect its implementation. Awareness of the legal implications of force majeure is very important for the parties involved in the agreement, to maintain clarity, fairness and order in the implementation of the agreement amid the dynamics of unforeseen circumstances. The Pacta Sunt Servanda principle in Indonesian treaty law is intended to provide equal rights for all parties involved in a contract. However, in force majeure conditions, this principle may not apply due to circumstances that prevent contract compliance. By using a normative juridical approach, this research aims to evaluate the effectiveness of the Pacta Sunt Servanda principle in force majeure. The results of this study show that force majeure is one of the factors that affect the effectiveness of the Pacta Sunt Servanda principle in Indonesian treaty law. Therefore, the application of the Pacta Sunt Servanda principle can be delayed due to force majeure. The consequences are the loss of rights and obligations of the agreement and the non-fulfillment of the rights and obligations stipulated in the contract.